Bigger is Surprisingly Better: Agglomerates of Larger RuP Nanoparticles Outperform Benchmark Pt Nanocatalysts for the Hydrogen Evolution Reaction. Issue 39 (21st August 2018) - Yu, Jie; Guo, Yanan; She, Sixuan; Miao, Shuanshuan; Ni, Meng; Zhou, Wei; Liu, Meilin; Shao, Zongping
Abstract: Although metallic ruthenium (Ru) is a potential electrocatalyst for the hydrogen evolution reaction (HER) to replace platinum (Pt) at a cost of only ≈4% of Pt, the persistent dissolution of Ru under operation conditions remains a challenge. Here, it is reported that agglomerates of large ruthenium phosphide (RuP) particles (L‐RP, ≈32 nm) show outstanding HER performance in pH‐universal electrolytes, which particularly demonstrates a surprisingly higher intrinsic activity and durability than small nanoparticles of RuP (S‐RP, ≈3 nm) or metallic Ru on carbon supports. This is especially true in basic media, achieving electrocatalytic activity comparable to or even outperforming that of Pt/C, as reflected by lower overpotential at 10 mA cm −2, smaller Tafel slope, larger exchange current density, and higher turnover frequency while maintaining 200 h stable operation. Calculations suggest that Δ G H* of RuP is much closer to zero than that of metallic Ru, and phosphorous doping is proven to enhance the rate of proton transfer in HER, contributing in part to the improved activity of RuP. The better performance of L‐RP than that of S‐RP is ascribed largely to the stabilization of the P species due to the lowered surface energy of large particles. Furthermore, the relatively low‐cost materials and facile synthesis make L‐RP/C a highly attractive next‐generation HER electrocatalyst. Abstract : Agglomerates of larger RuP nanoparticles, prepared by a facile one‐pot low‐temperature phosphorization route, perform surprisingly better than smaller ones for the hydrogen evolution reaction (HER) in a wide pH range. They even outperform benchmark Pt nanocatalysts, which makes the large RuP nanoparticles a highly attractive next‐generation HER electrocatalyst for hydrogen production through efficient water electrolysis.